PENGGUNAAN KEKERASAN DALAM PROSES PENYIDIKAN DILIHAT DARI PERSPEKTIF HUKUM DAN HAK ASASI MANUSIA - Yohanes Kevin Manik; R. Rahaditya (Fakultas Hukum Universitas Tarumanagara, 2020)
The police as a state agency have several tasks, one of them is to carry out investigations which will be helpful to find and collect evidence of a criminal act and its suspects. However, during the investigation process, the police tend to adjust violence to obtain evidence or confession from a person who suspected of committing a crime. Violence acts committed by the police can harm the suspect, in which the suspect has rights as a human being and as a community protected by laws and regulations. The police that committed violence acts against suspects can be santioned and/or sentenced based on the Police Professional Code of Ethics. The investigation process aims to provide clarity on a crime that has occurred. While carrying out the investigation process, the police assigned to look for evidence of a criminal act will interrogate the suspect. In the Article 52 of Criminal Procedure Code states that, during an investigation process a suspect has the right to provide information freely to the investigator.